Valorization of Citrus Co-Products: Recovery of Bioactive Compounds and Application in Meat and Meat Products - Gema Nieto; Juana Fernández-López; José A. Pérez-Álvarez; Rocío Peñalver; Gaspar Ros-Berruezo; Manuel Viuda-Martos (Plants, 2021)
Citrus fruits (orange, lemon, mandarin, and grapefruit) are one of the most extensively cultivated crops. Actually, fresh consumption far exceeds the demand and, subsequently, a great volume of the production is destined for the citrus-processing industries, which produce a huge quantity of co-products. These co-products, without proper treatment and disposal, might cause severe environmental problems. The co-products obtained from the citrus industry may be considered a very important source of high-added-value bioactive compounds that could be used in the pharmaceutical, cosmetic, and dietetic industries, and mainly in the food industry. Due to consumer demands, the food industry is exploring a new and economical source of bioactive compounds to develop novel foods with healthy properties. Thus, the aim of this review is to describe the possible benefits of citrus co-products as a source of bioactive compounds and their applications in the development of healthier meat and meat products.